Discourse on ageing in the autumn of life: language, identity, society and learning in a Lebanese nursing home - Ghandour, Hiba (2011)
This article describes a holistic investigation into aspects of the ageing process. It attempts to explore three different areas of enquiry that have served to centre clusters of research in the field: language and communicative abilities in old age; identity in old age; social values and practices in old age. It discusses a study of 20 residents in a nursing home in Beirut which aimed to investigate the use of narrative by the group to establish how different linguistic and communicative abilities, personal identities, and social values and practices had been shaped. It concludes by considering the implications for later life learning and research.